The relationship between ergonomic factors and stress outcomes among non-executive employees in social security organization (PERKESO) Kuching, Sarawak. / Beatrice Rex - Rex, Beatrice (2018)
The objective of this study was to identify the relationship between ergonomics factors and stress outcomes toward non-executive employees at the Social Security Organization (PERKESO) Kuching. The data collection method was a questionnaire survey and it distributed to non-executive employees. This study included 80 of the non- executive employees of PERKESO as the sample size. The respondents were from all departments that included Counter, Return to Work, Employee Insurance System, Finance, Enforcement, Rehab, Benefits and Administration/Publicity and they gave their responses on health, working chair, humidity, lighting, and working hours as the independent variables whereby stress outcome was the dependent variable. Reliability test for the instrument used was done using SPSS version 23.0. The outcome demonstrates that every element of Ergonomics Factors had a positive and negative significant correlation with Stress Outcomes. It is recommended that future analyst should expand the number of respondents and conduct future research in the ergonomics field more.